Learning Lessons Through Data Triangulation: Vulnerability of Surat City to HIV Epidemic - Anjali Modi; J K Kosambiya; H K Sondharwa; Manish Kumar (Medsci Publications, 2013)
Background: In context of increased data sources for monitoring the situation of HIV and decentralized planning, systemic appraisal is required by program managers to decide intervention strategies and formulate policies at the district and sub-district level. Materials and methods: The data triangulation exercise was carried at the District AIDS Prevention and Control Unit (DAPCU) and Surat AIDS Prevention and Control Unit (SAPCU) with stakeholders. A  twelve step approach to triangulation was followed which included identification and assessment of key questions, identification of data sources, refining questions, gathering data and reports, assessing the quality of those data and reports, formulating hypotheses to explain trends in the data, corroborating or refining working hypotheses, drawing conclusions, communicating results and recommendations and taking public health action. Results: The prevalence of HIV among ANC clinic attendees in HIV Sentinel Surveillance (HSS) and PPTCT 2008 was 0.76% and 0.9%. The HSS 2008 showed 14.40%, 4.4% and 10.00% positivity among high-risk groups (HRG); STI Clinic attendees, Female Sex Workers (FSW) and Men having Sex with Men (MSM). The observation of yearly trends showed stable to declining trends among general population and HRGs. Service (41.75%) and Treatment (21.42%) gaps at the program level for identifying and treating PLHIVs were found. Conclusion: The high HIV positivity of Surat city in comparison to the Gujarat state and India indicates its vulnerability towards HIV epidemic. The program officers and policy makers need to formulate special strategies to halt and reverse epidemic in Surat.